Health effects and user perceptions of the US Customs and Border Patrol One™ mobile application: A qualitative analysis among asylum seekers at the Mexico-US border - Christopher W. Reynolds; Brendon Tucker; Samuel Bishop; Sarah Draugelis; Michele Heisler; Amir M. Mohareb (Elsevier, 2024)
Background: The number of migrants at the Mexico-US border has increased to historic levels, and frequently changing immigration policy impacts this population as they await entry into the US. This study evaluated the usability and health effects of the Customs and Border Protection (CBP) One™ mobile application among asylum seekers near the US port of entry in Reynosa, Mexico. Methods: We conducted semi-structured qualitative interviews with 20 asylum seekers in Reynosa, Mexico, in February 2023. Our objective was to explore the subjective experiences of migrants, usability of CBP One™, and presence of perceived health effects from using the application. Interviews were conducted until saturation occurred, transcribed verbatim into Word, coded in NVivo using a validated, team-based coding methodology, and analyzed according to internal domains, external domains, and health effects regarding CBP One™. Results: Twenty participants originated from eight countries throughout Latin America and the Caribbean. In total, 18 subthemes were identified among internal, external, and effects domains. Internal themes included a confusing application interface (80%), technical malfunction (60%), and perceived racial bias from the photo-capture features (15%). External themes challenging CBP One™ use included unavailable appointment slots (80%), inequity and inaccessibility (35%), and inadequate internet (25%). Most perceived effects were negative (85%), including worsening mental health effects (40%), exacerbation of pre-existing physical conditions (35%), and forgoing health expenditures to pay for internet (25%). Conclusions: Our findings suggest that asylum seekers at the Reynosa port of entry perceive CBP One™ negatively, with detrimental effects towards their mental and physical health. This study highlights how immigration policy can influence health and suggests that more creative and humane approaches are needed for people seeking asylum at the Mexico-US border.